La cultura en las organizaciones: un fenómeno central en el saber administrativo - Podestá, Paola (2009)
This article is the result of empirical and bibliographical research processes about organizational culture. It relates some relevant aspects that, from the traditional perspective under which this concept has been understood, may be contrasted with more critical ones, such as that proposed by the Canadian school to which some of the authors researched belong. Likewise, this article may be considered a complement to one previously published by the author, also mentioned in the text.